THU0134 Left ventricular (LV) diastolic dysfunction associates with systemic inflammation in rheumatoid arthritis (RA). (1st June 2001) - Banks, MJ; Ahmed, F; Flint, EJ; Forsey, PR; Bacon, PA; Kitas, GD
Abstract : Background: Abnormal diastolic LV filling is an early marker of cardiovascular disease and death. In the general population, it associates with hypertension, LV hypertrophy or ischaemia. A high prevalence has been reported in RA and other inflammatory conditions (up to 40%), even after exclusion of patients with known, relevant cardiovascular pathology. Its cause and significance in inflammatory conditions remains unknown. Objectives: To identify the causes of diastolic LV dysfunction in RA. Methods: 39 random RA out-patients were assessed. LV filling: LV inflow Doppler in expiration by Echodoppler, with 5 measurements of isovolumetric relaxation time (IVRT), deceleration time (dte) and E:A ratio. Cardiac causes (BP, LVH, IHD ? age), Rose Questionnaire, examination, ECG, adenosine-stressed myocardial perfusion SPECT imaging. RA-related causes: acute phase response (current and mean ESR, CRP); cytokines (TNFa, Il-1b, Il-6); endothelial factors (vWF, ACE); Steroids: >7.5 mg Prednisone for >6 months; extra-articular disease. Statistics: Linear and multiple logistic regression as appropriate. Results: Age correlated significantly with IVRT (r = 0.444, p = 0.005), dte (r = 0.495, p = 0.003), and E:A ratio (r = 0.67, p = 0.0001). Mean ESR correlated with IVRT (r = 0.324, p = 0.04), Mean CRP with E:A ratio (r = 0.305, p = 0.05), Il-6 with E:A ratio (r = 0.34, p = 0.05), vWF with IVRT (r = 0.346, p = 0.03) and E:A ratio (r = 0.331, p = 0.04). E:A ratio was significantly lower in those on steroids. Multiple regression showed age and mean ESR to independently predict IVRT. vWF was collinear with mean ESR for IVRT. Age, Il-6, and mean CRP were independent predictors of E:A ratio. vWF and steroids were collinear with mean CRP for E:A ratio. Hypertension, LVH, IHD, BMI, RA duration and extra-articular features did not associate with LV filling in RA. The association of LV filling with inflammatory mediators remained significant even after correction for age. Conclusion: The association of worsening LV filling with inflammatory burden rather than established cardiovascular causes in RA is an interesting new observation. It may explain the previously reported high prevalence of abnormal LV filling in RA and other inflammatory conditions and may be due to direct cytokine effects on the myocardium.